2022
DOI: 10.1039/d2tb00687a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional silicon calcium phosphate composite scaffolds promote stem cell recruitment and bone regeneration

Abstract: Scaffold is one of the most significant implants for treating bone injury, while the precise control of stem cell proliferation and differentiation within scaffold is still challenging. In this work,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Xu et al also reported that a moderate pro-inflammatory microenvironment in the early stages after scaffold implantation contributed to stem cell recruitment. Alternatively, cell recruitment could be promoted by local administration [141,142] or in situ expression [143] of chemoattractants that are responsible for cell homing, as well as by physical cues (e.g., magnetic field) [144]; see Figure 5 for a schematic illustration. A protein proven to be both chemoattractive to bone-forming cells and pivotal to the development and regeneration of cranium is bone morphogenic protein-2 (BMP-2) [46].…”
Section: Enhancing the Osteogenic Potential On The Scalp Sidementioning
confidence: 99%
“…Xu et al also reported that a moderate pro-inflammatory microenvironment in the early stages after scaffold implantation contributed to stem cell recruitment. Alternatively, cell recruitment could be promoted by local administration [141,142] or in situ expression [143] of chemoattractants that are responsible for cell homing, as well as by physical cues (e.g., magnetic field) [144]; see Figure 5 for a schematic illustration. A protein proven to be both chemoattractive to bone-forming cells and pivotal to the development and regeneration of cranium is bone morphogenic protein-2 (BMP-2) [46].…”
Section: Enhancing the Osteogenic Potential On The Scalp Sidementioning
confidence: 99%